Research on Autonomous Guidance and Track Following Technology of Autonomous-rail Rapid Tram - PENG Jing; FENG Jianghua; XIAO Lei; REN Xiaojun; WANG Shanwei; LIU Xiaocong (Kongzhi Yu Xinxi Jishu)
Autonomous-rail rapid tram is a new type of urban rail transit. As a key technology, autonomous guidance and track following algorithm solves the problems of large proportion of road, poor flexibility, delayed steering and large errors during steering of multi-group articulated vehicle. The rapidity, accuracy and stability of the vehicle during steering are guaranteed. In this paper, the composition of the autonomous guidance system was firstly introduced, the control principle of tracking trajectory was proposed and the numerical model of steering system was established. Simulation analysis and experimental verification indicate that the system meets the response speed and trajectory tracking accuracy requirement of the vehicle during steering.